2023
DOI: 10.1112/plms.12510
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic asymptotic dimension and Matui's HK conjecture

Abstract: We prove that the homology groups of a principal ample groupoid vanish in dimensions greater than the dynamic asymptotic dimension of the groupoid (as a side-effect of our methods, we also give a new model of groupoid homology in terms of the Tor groups of homological algebra, which might be of independent interest). As a consequence, the K-theory of the đ¶ *algebras associated with groupoids of finite dynamic asymptotic dimension can be computed from the homology of the underlying groupoid. In particular, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(275 reference statements)
0
4
0
Order By: Relevance
“…Examples of recent research in this direction are the HK conjecture of Matui [35]a, or the relation between the homology theory of Smale spaces and the K -theory of their corresponding C * -algebras [52]. In this latter example, a special case of the methods developed here (i.e., when the groupoid is torsion-free and ample) has already been applied with great success and lead to many interesting results in topological dynamics, as is demonstrated by the papers [9,49,51,50].…”
Section: Introduction and Main Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Examples of recent research in this direction are the HK conjecture of Matui [35]a, or the relation between the homology theory of Smale spaces and the K -theory of their corresponding C * -algebras [52]. In this latter example, a special case of the methods developed here (i.e., when the groupoid is torsion-free and ample) has already been applied with great success and lead to many interesting results in topological dynamics, as is demonstrated by the papers [9,49,51,50].…”
Section: Introduction and Main Resultsmentioning
confidence: 79%
“…In many applications, however, it is useful to have a concrete model at hand. This is certainly the case for the adjunction result in Theorem 2.3 below but has also proven to be a useful construction in [49,9].…”
Section: The Induction Functormentioning
confidence: 79%
“…It is also closely related to the diagonal dimension of sub-C * -algebras recently introduced in [14]. In [3] it was shown that the groupoid homology groups of a totally disconnected Ă©tale groupoid vanish in all degrees exceeding the dynamic asymptotic dimension of the groupoid. Estimates on the dynamic asymptotic dimension (denoted henceforth by dad(‱)) are known for many concrete classes of examples (see e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Remark 6.11. We note that there exist maps ÎŒ i : H i (G) → K i (C * r G) for i = 0, 1 in the case of ample groupoids, and they have been studied in [BDGW23,Mat12]. For higher degrees, one can still construct analogous maps by looking at kernels of higher differentials from the associated spectral sequence from [PY22a].…”
mentioning
confidence: 99%